Multi-unit franchising: Growth and management issues - Kaufmann, Patrick J.; Dant, Rajiv P. (Journal of Business Venturing, 1996)
Entrepreneurs in a number of retailing sectors have eschewed the creation of company-owned chains and have embraced franchising as a preferred method for growing their businesses. There have been two leading reasons proposed for this preference. First, that franchisees provide the financial capital necessary for expansion, and second that franchisees manage the outlets better than company employees would if the unit were company owned. Interestingly, although many entrepreneur/franchisors confirm the relevance of the capital acquisition argument in their decision-making, theoretical analysis has discounted its importance. Instead, researchers have focused on the incentives of employee store-managers to misrepresent their ability and their effort as the dominant impetus behind franchising. Misrepresentation by employees as to ability and effort imposes costs and inefficiencies on the entrepreneur's chain. Arguing that franchising solves these problems by having the stores managed by persons with claims to the profits, these researchers have, by and large, rejected the capital acquisition argument for franchising in favor of this incentive-based rationale. Within this view, multi-unit franchising presents a curious anomaly. Multi-unit franchising, either through the incremental expansion by the franchisee one unit at a time or through the rights to open multiple units contained in an area development agreement, creates a collection of mini-chains within the franchise system. These mini-chains are operated by employee store-managers. Of course, they are employees of the franchisee, but they are employees nonetheless, and as franchise researchers have traditionally argued regarding the entrepreneur's employees, they will have incentives to misrepresent their ability and effort. Moreover, multi-unit franchising is ubiquitous. If multi-unit franchising is at odds with the incentive rationale for franchising, and it has a positive association with the growth of franchise systems, it must be providing the entrepreneur with some other benefit. In this study, we argue that the benefit it provides is access to capital. Through a study of fast-food franchise systems, we demonstrate that the more a chain engages in multi-unit franchising (i.e., the greater the proportion of multi-unit franchisees it has), the faster it grows, even faster than franchise systems generally. Moreover, we show that the level of commitment franchisors feel toward continuing to franchise is negatively related to the average number of units per franchisee and negatively related to their ability to obtain financial capital elsewhere. In other words, although multi-unit franchising helps an entrepreneur grow his or her business by providing increased access to capital, store level incentive problems get increasingly troublesome as franchisees get more and more units. It would appear, therefore, that capital acquisition is a relevant reason for engaging in franchising after all.